Parental exposure to childhood maltreatment and offspring’s mental health: investigating pathways through parental adversity and offspring exposure to maltreatment - Negriff, Sonya (Child maltreatment, 2020)
Parental exposure to child maltreatment (CM) is an important predictor of their offspring?s CM experiences and mental health. However, less attention has been paid to examine possible mechanisms of transmission, which is critical to inform prevention and intervention efforts. The current study tested (1) whether the association between parental CM exposure and offspring CM exposure was mediated by (a) parental exposure to violence in adulthood or (b) other emotional stressors/adversities in adulthood and (2) the indirect effects from parental CM exposure to offspring mental health outcomes through parental adversity and offspring CM exposure. Data came from a longitudinal study of maltreatment on adolescent development, and analyses focused on adolescents living with a biological parent (N = 185, 51% female). Biological parents (95% mothers) reported on their history of CM and exposure to other adversities across their lifetime. Adolescents self-reported lifetime CM experiences and current depression, anxiety, posttraumatic stress disorder, and externalizing behaviors in late adolescence (M age = 18.49). Results showed a significant indirect effect of parent CM exposure on offspring?s CM exposure and mental health through parental emotional stressors/adversities, but not physical violence. These findings highlight different types of stressors that may impact the risk for intergenerational transmission of CM and subsequent offspring mental health.